Un nouveau cachet à collyres découvert à Reims/Durocortorum - Muriel Pardon-Labonnelie; Magalie Cavé; Aurélie Troublard (Gallia)
A new eyedrop cachet was discovered during the excavation of the aquatic complex of Reims by Inrap in 2018. It presents exceptional morphological and epigraphic features. Like the majority of the other 365 eyedrop cachets recorded to date, this one is a rectangular parallelepiped with a square cross-section, cut from shiny grey-green rock –most likely fine-grained greywacke– the edges of which have been chamfered on the two largest sides. Its texts are particularly interesting in regards to the history of medicine. Firstly, the use of the following terms for eye drops: diamys(us), croco(des) and euodes, confirm the inclusion of Roman medicine in the Greek therapeutic tradition. Secondly, these inscriptions also reveal the name of a new practitioner: Lucius Iulius Verus. Finally, the inscriptions also include a new term for eye drops: uamomatum. The reuse of the chamfered edges for the imprint of a new practitioner’s name is, to this day, without equivalent. The discovery of Lucius Iulius Verus’ eyedrop cachet confirms the incomparable role of Reims/Durocortorum in the history of Greco-Roman ophthalmology. To date, this eye-drop cachet is the fifteenth to be unearthed from the subsoil of Reims and was found less than 300 m from the C(aius) Censori(us) Verus stone. If this placement is not fortuitous, two practitioners bearing the same cognomen is a coincidence attesting to a professional filiation that is all the more fascinating, as it is entirely unique.